A randomized, placebo‐controlled study of the NS5B inhibitor beclabuvir with peginterferon/ribavirin for HCV genotype 1. Issue 8 (15th December 2014) - Tatum, H.; Thuluvath, P. J.; Lawitz, E.; Martorell, C.; DeMicco, M.; Cohen, S.; Rustgi, V.; Ravendhran, N.; Ghalib, R.; Hanson, J.; Zamparo, J.; Zhao, J.; et al.
Summary Beclabuvir is a potent, non‐nucleoside inhibitor of the HCV NS5B RNA polymerase, with nanomolar activity against HCV genotypes 1, 3, 4, 5 and 6 in vitro. This study evaluated the efficacy and safety of beclabuvir, in combination with peginterferon alfa‐2a (pegIFN) and ribavirin (RBV), in HCV genotype 1. In this randomized (1:1:1), double‐blinded, placebo‐controlled, dose‐ranging phase 2a study, 39 treatment‐naive patients chronically infected with HCV genotype 1 were treated for 48 weeks with beclabuvir (75 mg or 150 mg) plus pegIFN (180 μg) and RBV (1000 mg/day [<75 kg] or 1200 mg/day [≥75 kg]) vs pegIFN/RBV alone. The primary efficacy endpoint of extended rapid virologic response (undetectable HCV RNA at treatment weeks 4 and 12) was achieved by 76.9% (10/13) of patients receiving beclabuvir 75 mg and 38.5% (5/13) receiving beclabuvir 150 mg vs 0% receiving pegIFN/RBV alone. Higher response rates were observed among patients receiving beclabuvir 75 mg for all secondary efficacy endpoints, including sustained virologic response at follow‐up weeks 12 or 24. Three patients experienced virologic breakthrough on treatment, all in the beclabuvir 150‐mg treatment group. Beclabuvir was well tolerated at both doses, with the most commonly observed adverse events (headache, fatigue, nausea, decreased appetite, irritability, depression and insomnia) consistent with those observed with pegIFN/RBV. In conclusion, beclabuvir was both effective and well tolerated when administered in combination with pegIFN/RBV for the treatment of chronic HCV GT 1, supporting the study of beclabuvir as part of an all‐oral regimen for HCV GT1.